Purification and physicochemical properties of Bacillus sp. IMB B 7883 proteases - Varbanets, L.D.; Gudzenko, O.V. (Problems of Environmental Biotechnology, 2023)
The aim of the work was to isolate and purify these enzymes from the supernatant of the culture liquid of the producer strain Bacillus sp. IMV B-7883, as well as to study their physical and chemical properties and substrate specificity. Isolation and purification of the proteolytic complex of Bacillus sp. IMV B-7883 was carried out by classical biochemical methods: precipitation of the supernatant of the culture liquid with ammonium sulfate of 90% saturation, gel permeation and ion exchange chromatography and rechromatography on Sepharose 6B. As a result, elastase activity was increased by 63.6 times (4138 U/mg of protein) and fibrinogenolytic activity by 44.07 times (833 U/mg of protein). Like enzymes from other well-known producers, the investigated proteases were of low molecular weight, 23 and 20 kDa, respectively, for the protease with elastolytic and fibrinogenolytic activity. Unlike the elastases described in the literature, which are alkaline proteases, the enzyme with elastase activity had a pH-optimum of 7.0, while the enzyme with fibrinogenolytic activity was an alkaline protease with a pH-optimum of 8.0. Research on substrate specificity of enzymes showed the protease with elastase activity hydrolyzed only elastin, while the protease with fibrinogenolytic activity, in addition to fibrinogen, showed specificity also for fibrin and, in trace amounts, for collagen.